Advances in environmental science: a review of IJE papers (Vol. 3, Iss. 1 & 2) - Punati, Naveen; Rao, Ajith (International Journal of Environment, 2015)
DOI: http://dx.doi.org/10.3126/ije.v4i2.12665 International Journal of Environment Vol.4(2) 2015: 374-393